If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + -3x = -1x + -5 Reorder the terms: -1 + -3x = -5 + -1x Solving -1 + -3x = -5 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -1 + -3x + x = -5 + -1x + x Combine like terms: -3x + x = -2x -1 + -2x = -5 + -1x + x Combine like terms: -1x + x = 0 -1 + -2x = -5 + 0 -1 + -2x = -5 Add '1' to each side of the equation. -1 + 1 + -2x = -5 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = -5 + 1 -2x = -5 + 1 Combine like terms: -5 + 1 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| n/0.3=66.6666666666 | | x-11(x)=80 | | x^2-22x+121=255 | | 2(3x+6)-5x=14 | | n/.3=662/3 | | 6n-14=4 | | 4x-6=11x+16 | | 3x(x)=70 | | y+26=2y+8 | | 16-7x=-5x-4x | | 4(y+1)=2y+3+2y | | ln(x)=-1.082238098 | | y+26=2y+8-4 | | 125=-16t^2+125t+4 | | t+96=117 | | -7n+2=10 | | Y+8=2(x+4) | | 10x-2=181 | | 3(n+5)=4n+10-n+5 | | 8y^2+30+13= | | 13x-6x+15=6x+11 | | 123=-16t^2+123t+5 | | .12x-1=2+.75x | | n^2=3-2n | | 156=92-y | | Y=x^4+3x^2 | | m^2+10m=-21 | | 2x-(12)=4 | | -3h+14=8-h | | x^2=-6+7x | | .36(6)+.05x=.10(18+x) | | 8m-12=4+7m |